2013
DOI: 10.1007/s11999-013-2872-3
|View full text |Cite
|
Sign up to set email alerts
|

Method of Fixation Does Not Influence the Overall Risk of Rerevision in First-time Cup Revisions

Abstract: Background During the last two decades, uncemented fixation has been increasingly preferred worldwide during cup revision surgery. In Sweden, the number of uncemented cup revisions has been increasing during the last decade. However, it is unclear whether the risk of rerevision differs between cemented and uncemented cups. Question/purposes We determined (1) the risk of rerevision after cemented and uncemented fixation; (2) the influence of concomitant stem revision on the risk of rerevision of the cup; (3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
2
10
2
Order By: Relevance
“…Using the same technique on 142 acetabular reconstructions, Comba et al (2006) reported a survival rate of 96% at a mean follow-up time of 4.3 years. In a recently published study ( Mohaddes et al 2013 ) from the SHAR, we could not find any difference in risk of re-revision between cemented and uncemented first-time cup revisions. According to the current analysis, the risk of re-revision was lower for the cemented Lubinus cup than for the Trilogy cup.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Using the same technique on 142 acetabular reconstructions, Comba et al (2006) reported a survival rate of 96% at a mean follow-up time of 4.3 years. In a recently published study ( Mohaddes et al 2013 ) from the SHAR, we could not find any difference in risk of re-revision between cemented and uncemented first-time cup revisions. According to the current analysis, the risk of re-revision was lower for the cemented Lubinus cup than for the Trilogy cup.…”
Section: Discussioncontrasting
confidence: 61%
“…According to several reports ( Kurtz et al 2007 , Pabinger and Geissler 2014 ) an increase in revision hip arthroplasties is expected. During the past 2 decades, the number of hip revision surgeries reported to the Swedish Hip Arthroplasty Register (SHAR) has doubled ( Mohaddes et al 2013 ).…”
mentioning
confidence: 99%
“…Approximately 70% of all index revisions were a partial revision, where in the majority of these procedures either the cup or the stem was replaced (major partial revision). Failure rate of the minor partial revisions (replacement of head and/or insert) was higher when compared with major partial revisions or total revisions, which is supported by data from the Swedish Hip Arthroplasty Register (Mohaddes et al 2013). A possible explanation for this might be the high percentage of index revisions with reason given as infection using this method, or the exchange of heads to prevent further dislocations.…”
Section: Comparison With Literaturesupporting
confidence: 53%
“…Third, our mean followup was only 3 years, which is a relatively short time in a hip implant's lifespan. However, uncemented revision cups more often are associated with higher early revision rates, whereas cemented cups often are associated with later wear-related problems [11]. In addition, the risk of rerevision resulting from infection is higher during the early period after the first revision [14].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggesting inferior implant survival when cemented acetabular components are used in revision THA led to increased use of uncemented acetabular cups in first-time revision THA during the last two decades [17]. Although uncemented cups made from porous tantalum initially were designed to help manage challenging bone deficiencies, there is evidence that they are seeing wide use for revision and primary THAs [11,13]. Porous tantalum has been shown to provide higher porosity, increased initial stability, and better bone ingrowth qualities [2].…”
Section: Introductionmentioning
confidence: 99%